Integrasi Nilai Akhlak dan Sportivitas melalui Pembelajaran Penjas Berbasis Permainan Tradisional - M. Asri B (Lembaga Yasin AlSys, 2026)
Physical Education has strong pedagogical potential to develop character through direct experiences of complying with rules, competing, cooperating, making rapid decisions, and confronting social consequences. This study aims to analyze the effectiveness of traditional game-based Physical Education instruction that explicitly integrates moral values, including honesty, trustworthiness, justice, self-control, respect, and ta‘āwun, in improving sportsmanship and cooperation among students in the Primary School Teacher Education Program at Universitas Negeri Makassar. The study employs a mixed-methods approach with a quasi-experimental design involving an intervention group and a comparison group, as well as pretest–posttest measurements. Data were collected through measurements of sportsmanship and cooperation, behavioral observations, and students’ written reflections. Moral values were operationalized through game rules, role rotation, conflict-resolution mechanisms, post-activity reflection, and behavioral assessment. Quantitative data were analyzed to examine changes in sportsmanship and cooperation, whereas qualitative data were analyzed thematically to explain how students interpreted competitive dilemmas and pedagogical responsibilities. Because the results presented in the manuscript are still based on simulated data, empirical conclusions regarding the effectiveness of the intervention cannot yet be established, and all such results must be replaced with field data. Conceptually, this study offers a character education framework that connects normative values with embodied learning practices in Physical Education for prospective primary school teachers.